Method of Determination of Technological Durabilityof Plastically Deformed Sheet Parts of Vehicles - Dragobetskii, Volodymyr; Zagirnyak, Mykhaylo; Naumova, Olena; Shlyk, Sergii; Shapoval, Aleksandr (International Journal of Engineering and Technology, 2018)
The purpose of the article is to develop an apparatus providing maximum or predicted durability of parts treated during their manufacture by plastic deformation. In these terms, the parameters of the technological process should provide the maximum or expected increase of the endurance limit in comparison with the initial parts values before the strengthening by the surface plastic deformation or after plastic forming. The article describes the influence of the degree of preliminary deformation on the kinetics of fatigue failure of metals and alloys. Experimental data of the ultimate deformations of welded workpieces were obtained, which make it possible to evaluate the manufacturing of parts with a weld seam at the design stage of the technological process. The developed method made it possible to determine the nonstationary field of stresses in the deformation region, ultimate deformations and the most rational scheme of the stress-strain state, which excludes the localization of deformations and destruction of the weld zone of a welded cylindrical workpieces.Â Â